Oxidaton of 1,4-Dihydropyridines under Mild and Heterogeneous Conditions - Ali Zolfigol, Mohammad; M. Sadeghi, Majid; Mohammadpoor-Baltork, Iraj; Ghorbani Choghmarani, Arash; Taqian-Nasab, Abolfazi (Asian Journal of Chemistry, 2010)
A combination of NaHSO4·H2O and (NH4)2Cr2O7 in the presence of wet SiO2 was used as an effective"oxidizing agent for the oxidation of 1,4-dihydropy'ridines to their corresponding pyridine derivatives at room temperature with excellent yields.